Improving Client Satisfaction Through New Patient Orientation Using Flipchart Media - Thusholihah, Mike Irmalina; Putri, Prestasianita; Permana, Roby Aji (Journal of Nursing and Midwifery Sciences, 2025)
Low client satisfaction leads to a decline in hospital visits. The explanation of nursing services serves as the initial interaction between clients and nurses, which influences client satisfaction and can subsequently increase hospital visits. This study aims to analyze the implementation of new patient orientation using flipchart media on client satisfaction at Kalisat Regional Hospital. The research method used in this study is a quasi-experimental design with a two-group pretest-posttest approach. The study population consisted of 106 patient families in the Manyar Ward. The sample was selected using purposive sampling, with 26 individuals in the intervention group and 26 in the control group. The instrument used was a validated and reliable questionnaire. Statistical analysis was conducted using the Wilcoxon matched-pairs test and the Mann-Whitney test. In the control group, the level of satisfaction before orientation showed 42.3% dissatisfaction and 53.8% satisfaction. After the orientation, 53.8% of respondents reported satisfaction. In the intervention group, the pre-orientation satisfaction level was 19.2% dissatisfied and 80.8% satisfied, whereas post-orientation, 15.4% were satisfied and 84.6% were very satisfied. This study demonstrates that implementing new patient orientation using flipchart media has a significant impact on client satisfaction at Kalisat Regional Hospital, Jember. Orientation using flipchart media can be an effective method to enhance client satisfaction